Bilateral Elongated Mandibular Coronoid Process and Restricted Mouth Opening: A Case Report - Starch-Jensen, Thomas (Open Dent J, 2017)
INTRODUCTION: Mandibular coronoid process hyperplasia is an uncommon congenital or developmental temporomandibular joint disorder, characterized by elongation of the coronoid process, which may cause limited mandibular movement as a consequence of interference between the hyperplastic coronoid process and the medial surface of the zygomatic arch. METHODS: Mandibular coronoid process hyperplasia commonly affects males in the second decade of life and the exact aetiology and pathogenesis is unknown. The condition can be uni- or bilateral. Progressive painless reduction in mouth opening is the main clinical finding and computed tomography is the most reliable imaging modality for confirming the diagnosis. RESULTS: Surgical intervention involving coronoidectomy and long-term intensive postoperative physiotherapy is the treatment of choice for mandibular coronoid process hyperplasia with impingement on the zygomatic bone and limited mouth opening. However, surgically induced fibrosis and the tendency for mandibular coronoid process regrowth may cause relapse and renewed limited mouth opening. Vigorous physical therapy should therefore be initiated shortly after surgery. CONCLUSION: The purpose of this case report is to present the clinical and radiographic features of elongated mandibular coronoid process in an 18-year-old male with limited mouth opening, and to discuss the various surgical treatment modalities.